PROBLEMATIKA MEDIASI PADA KASUS PERCERAIAN KARENA ADANYA PIHAK KETIGA DI PENGADILAN AGAMA ENREKANG PERSPEKTIF HUKUM ISLAM - Andi Sartika jufri; Lomba Sultan; Fatmawati (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
Abstract Mediation Problems in Divorce Cases Due to the presence of a third party at the Enrekang Religious Court from an Islamic Law Perspective. The author examines the problems of the mediation process in the divorce case because of the existence of a thrid party at the Enrekang Religios Court, and the obstacles faced in the process of resvolving the mediation in the divorce case due to the presence of a third party at the Enrekang Religious Court andi the view of Islamic law on the problems of mediation in the divorce case due to the presence of a third party. This research is decriptive qualitative in the form of filed research or research files which is carried out by going directly to the research location to obtain anda collect complete and valid research data, the data collection methods used are observation, interviews and dokumentation. The results of the study show that the mediation process at the Enrekang Religious Court has similarities in the mediation process in general but in it’s application there are differences and the types of cases handled, the contraints that cause, mediation to fail are the emergence of internal problems in husband and wife marriages, loq levels of education, lock of moral understanding and Religion, difficult to work, low levels of education, lack of moral understanding and Religion, difficult to work with and the absence of one party, already has a partner. Keywords: Mediation, Divorce, Third Parties, Islamic law